Thermal Analysis Of Micro Heat Pipes : Effects Of Geometry, Type Of Working Fluid, And Gravity - D, Sugumar (2002)
This thesis is devoted to the thermal analysis of a micro heat pipe. In this thesis, the thermal analysis concerns with the heat transport capacity of a micro heat pipe. Therefore, the effects of diffrent types of design and operating parameters, such as type of working fluid, geometry and gravity are investigated on the heat transport capacity of a micro heat pipe.